1994
DOI: 10.1016/0735-1097(94)90101-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized prospective evaluation of prolonged versus abbreviated intravenous heparin therapy after coronary angioplasty

Abstract: Omission of routine heparin therapy after successful coronary angioplasty reduces bleeding complications without increasing patient risk. Earlier discharge and significant cost savings are possible under proper conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 32 publications
2
38
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12] The transradial arterial approach (TRA), which is a fairly simple route of access 13,14 for catheter-based coronary intervention, has been developed for more than 15 years and since the safety and efficacy of this method was fully discussed and validated, 13,15 it has become a widely used approach, especially in Asia, for elective percutaneous coronary intervention (PCI). [15][16][17][18][19] Recent studies has further indicated that TRA is safe and efficacious for elective coronary angiographic studies of outpatients, 20 elective left main coronary intervention, 21 cerebral angiographic studies or vertebral or carotid stenting.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12] The transradial arterial approach (TRA), which is a fairly simple route of access 13,14 for catheter-based coronary intervention, has been developed for more than 15 years and since the safety and efficacy of this method was fully discussed and validated, 13,15 it has become a widely used approach, especially in Asia, for elective percutaneous coronary intervention (PCI). [15][16][17][18][19] Recent studies has further indicated that TRA is safe and efficacious for elective coronary angiographic studies of outpatients, 20 elective left main coronary intervention, 21 cerebral angiographic studies or vertebral or carotid stenting.…”
mentioning
confidence: 99%
“…Depending on access site [5][6][7], size of introducer sheath [3,8], and coagulation status [9][10][11] vascular interventional procedures are associated with access site complications such as formation of hematomas, pseudoaneurysms, or arteriovenous fistulas. Therefore, anticoagulation, thrombocytopenia, and other bleeding disorders can be contraindications for an indicated angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Friedman et al [36] evaluated 238 patients with stable angina who were randomized to receive a 24-hr heparin infusion or no additional heparin after uncomplicated angioplasty. Prolonged heparin therapy not only failed to reduce the occurrence of acute ischemic complications but was associated with a 7% rate of bleeding complications, compared with no such complications among patients receiving abbreviated therapy (P Ͻ 0.001).…”
Section: Heparin Infusionmentioning
confidence: 99%